Pengaruh Media terhadap BudayaTradisionil, Lokal, Kontemporer dan Budaya Popular - Amal, Riski (At-Tabayyuun: Journal Islamic Studies, 2019)
Culture is derived from the word buddhayah (Sanskrit), meaning the mind or intellect. In Latin, the word culture comes from Colere, which berartti tilling the soil. So culture in general can be interpreted as "everything that is produced by the intellect (mind) of man with the aim to meet the needs of life and the environment". Culture theory that includes the theory of Selective Process and Cultivation theory role of the media see the mass media as a window on events and experriece. The media is seen as a window that allows the audience to see what is happening there. Or media is a means to learn to know the different events. How does the media influence of traditional culture and local culture of Indonesia and created a new culture of contemporary or contemporary and more violent or global pop culture that began infecting every culture in the world, in particular Indonesian Aceh alone. How can we be wise and positive in dealing with any new culture and preserve the old culture.